Lung cancer. Issue 3 (March 2023) - Mhandu, Peter; McGonigle, Niall
Abstract: Lung cancer remains the greatest cause of cancer-related death in the United Kingdom despite its lower incidence compared to other cancers. It remains very treatable with excellent outcomes in the early stages; however, many patients present with late symptoms. Investigation of lung cancer has changed significantly over the last decade to allow less invasive staging techniques and, more importantly, less invasive operative techniques to allow surgery in patients that may have previously been denied surgery.